1994
DOI: 10.1523/jneurosci.14-04-02290.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the choline acetyltransferase structural gene (cha-1) from C. elegans

Abstract: We have cloned the cha-1 gene from Caenorhabditis elegans using the method of transposon tagging, cha-1 is the structural gene for ChAT, the enzyme that synthesizes ACh. Sequence analysis of cDNAs predicts a protein of 71.5 kDa; comparison of the deduced amino acid sequence with ChAT sequences from other species confirms that cha-1 encodes ChAT. Comparison of cDNA and genomic sequences reveals that transcription is from right to left on the genetic map, and that some of the transcripts may result from trans-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…Animals homozygous for this mutation are viable, and their growth and development appear to be normal, although they are slightly long and thin. Since cholinergic neurotransmission is essential for viability in C. elegans (Alfonso et al 1993(Alfonso et al , 1994, we conclude that the CHO-1 protein is not essential for cholinergic function.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Animals homozygous for this mutation are viable, and their growth and development appear to be normal, although they are slightly long and thin. Since cholinergic neurotransmission is essential for viability in C. elegans (Alfonso et al 1993(Alfonso et al , 1994, we conclude that the CHO-1 protein is not essential for cholinergic function.…”
Section: Resultsmentioning
confidence: 79%
“…The relatively mild phenotype of cho-1 mutants was therefore surprising, since cholinergic neurotransmission is essential for viability in C. elegans (Alfonso et al 1993(Alfonso et al , 1994. Clearly, in the absence of cho-1 function, choline for ACh synthesis must be supplied in other ways, either through other transporters, or by de novo synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3d). eat-2 encodes an ionotropic ACh receptor that is expressed in the MC-pharyngeal muscle neuron junction 30 ; thus, an eat-2 null mutation blocks cholinergic transmission from the MC to the pharyngeal muscles 31 ; cha-1 encodes a choline acetyltransferase that synthesizes the neurotransmitter ACh 32 and a cha-1 mutation results in reduced ACh. To test if tmc-1 and eat-2 act in the same pathway, we made an eat-2(ad1113); tmc-1(ok1859) double mutant and found that 39% (n ¼ 102) develop into adults at 4 d.p.h.…”
Section: Tmc-1 Functions To Retard Growth On Cemmmentioning
confidence: 99%
“…Following transmitter release, cholinergic signaling is terminated primarily through the action of acetylcholinesterase (AChE), which hydrolyses the released ACh into choline and acetyl-CoA. In the nematode Caenorhabditis elegans, the ChAT and VAChT proteins are encoded by the cha-1 and unc-17 genes, respectively (Alfonso et al , 1994b. Mutations that functionally eliminate either protein are lethal , while reduction-of-function mutations result in animals that are small, slow growing, uncoordinated, and resistant to AChE inhibitors such as aldicarb .…”
mentioning
confidence: 99%